PENGARUH SOCIAL MEDIA, WORD OF MOUTH DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI CAFE SUNSET PALM.ID DI KABUPATEN PINRANG - Haisya Hambali; Amir Mahmud; Ackhriansyah Achmad Gani (Center of Economic Students Journal, 2023)
This study aims to analyze the influence of social media, word of mouth, and service quality on people's purchasing decisions at Cafe Sunset Palm.id in Pinrang Regency. This study uses a quantitative method with a descriptive approach and a survey of 85 respondents, consisting of 76.7% women and 23.3% men. The majority of respondents are in the age range of 18-25 years as much as 42.5% and work as Civil Servants (PNS) as much as 50%. The research variables were analyzed using descriptive analysis and categorization of respondent answers. The results showed that the social media variable obtained an average score of 4.59, which means that most respondents strongly agree that social media influences their purchasing decisions. The word of mouth variable received an average score of 4.64, indicating a very strong influence on purchasing decisions based on recommendations from others. The service quality variable had an average score of 4.52, indicating that respondents pay close attention to service quality before deciding to buy a product. While the purchasing decision variable itself received an average score of 4.57, indicating that most respondents were in the agree to strongly agree category in making purchasing decisions. Thus, it can be concluded that social media, word of mouth, and service quality have a positive effect on purchasing decisions, where word of mouth is the most dominant variable. This finding is expected to be a reference for business actors to improve marketing strategies and service quality in order to improve consumer purchasing decisions.